THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY ON LOCALS; THE CASE OF THE HOSPITALITY SECTOR IN CRETE - Alexandros Apostolakis; Corina Daniil; Markos Kourgiantakis (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
The current paper focuses upon the impact of Corporate Social Responsibility (CSR) on locals’ opinions regarding the hospitality sector in Crete. The main research aim driving the current study is to evaluate respondents’ (locals’) willingness to pay a premium for CSR activities in the hospitality sector. The paper utilizes primary data collected through a survey questionnaire in the region of Crete. In total, researchers collected 400 survey questionnaires over a course of three months during the pandemic period. The paper utilized a logistic regression framework. According to the results, respondents that were highly familiar with CSR were also very positive in supporting CSR actions. Whereas gender does not seem to exert a particularly strong influence on individual willingness to pay a CSR premium, yet once the analysis distinguishes between different premium levels, females were found more likely to contribute at lower amounts, as compared to their male counterparts. The results indicate that businesses should adopt and adapt their CSR practices to new business discourses.